Análisis markoviano de las sucesiones de abanicos aluviales de la cuenca de Madrid y de la depresión intermedia (Madrid y Guadalajara, España Central) - Peláez, A.; Coello, F.J.; Torres, T.; García-sañudo, M.; Nestares, T.; Ortiz, J.E. (Cuadernos de Geología Ibérica, 1996)
We have applied Markov chain analysis to Neogene stratigraphical sucessions from Madrid and Depresion Intermedia basins. Data were obtained from borehole lithologs comprising alluvial fan and mud fiat playa deposits. Markov chain analysis allows to determine repetitive process through time sad space and, in this case, to detect stages (facies> which apparence is linked Cuadernos de Geología Ibónca, núm. 21, Pp. 345-368. Servicio de Publicaciones. Universidad CompIutec~se, Madrid, 1996. 346 11 Ten-es el al. tú the inmediately preceeding stage (facies>. The method comprises transition-count matrix, independent trials matrtx and proportional difference matrix calculation, as well as Chi-square test calculation. Por each borehole litholog significative facies sucession were calculated and described, others were rejected.
Keywords: Neogene; alluvial fan; mud fiat; Markov anailysis